Alasan Menolak Mutasi menjadi Dasar Pemutusan Hubungan Kerja menurut Undang- Undang Nomor 13 Tentang Ketenagakerjaan dan Peraturan Pemerintah Nomor 35 Tahun 2021 - Prasetyo, Rachmad Andi; Haryono, Dipo Wahjoeono (CV. Era Digital Nusantara, 2025)
In industrial relations practices, job transfers or reassignment of duties are essential tools used by employers to manage human resources efficiently. Job transfer involves the reassignment of an employee’s position or work location for various reasons, such as operational efficiency or career development. However, employees may refuse the transfer, potentially leading to conflict and possibly resulting in Termination of Employment (TOE). According to Indonesia’s Law Number 13 of 2003 on Labor and Government Regulation Number 35 of 2021, transfer refusal must adhere to specific procedures to avoid TOE. These regulations ensure that job transfers are conducted fairly, respecting employee rights, and require bipartite or tripartite negotiation in case of disputes. When transfer refusal leads to TOE, employees are entitled to fair compensation per employment regulations. This study aims to examine the legal implications of transfer refusal on employment status and how applicable legal procedures protect workers' rights within industrial relations.